2012
DOI: 10.1111/1365-2745.12037
|View full text |Cite
|
Sign up to set email alerts
|

Enemy damage of exotic plant species is similar to that of natives and increases with productivity

Abstract: Summary1. In their colonized ranges, exotic plants may be released from some of the herbivores or pathogens of their home ranges but these can be replaced by novel enemies. It is of basic and practical interest to understand which characteristics of invaded communities control accumulation of the new pests. Key questions are whether enemy load on exotic species is smaller than on native competitors as suggested by the enemy release hypothesis (ERH) and whether this difference is most pronounced in resource-ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 72 publications
3
22
0
Order By: Relevance
“…Similar observations had been previously made by a large number of authors (e.g., Carpenter and Cappuccino 2005;Liu and Stiling 2006;Parker and Gilbert 2007;Proches et al 2008;Sugiura 2010;Harvey et al 2012;Litt et al 2014;van Hengstum et al 2014;Cronin et al 2015). However, in a significant amount of other studies, no difference in herbivory damage or abundance was found between native and exotic plants, especially when only congeneric native and exotic plant species were compared (e.g., Novotny et al 2003;Hawkes 2007;Sugiura et al 2008;Chun et al 2010;Dostál et al 2013), suggesting that the release from herbivory in the region of introduction is not a general pattern for exotic plants (Bezemer et al 2014). The herbivores' feeding guild also plays a role, with endophagous insects, such as leaf miners, bud borers or gall makers, showing a stronger preference for native plants than external feeders, probably because of their higher specificity (Kulfan et al 2010;Burghardt and Tallamy 2013;Kirichenko et al 2013).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Similar observations had been previously made by a large number of authors (e.g., Carpenter and Cappuccino 2005;Liu and Stiling 2006;Parker and Gilbert 2007;Proches et al 2008;Sugiura 2010;Harvey et al 2012;Litt et al 2014;van Hengstum et al 2014;Cronin et al 2015). However, in a significant amount of other studies, no difference in herbivory damage or abundance was found between native and exotic plants, especially when only congeneric native and exotic plant species were compared (e.g., Novotny et al 2003;Hawkes 2007;Sugiura et al 2008;Chun et al 2010;Dostál et al 2013), suggesting that the release from herbivory in the region of introduction is not a general pattern for exotic plants (Bezemer et al 2014). The herbivores' feeding guild also plays a role, with endophagous insects, such as leaf miners, bud borers or gall makers, showing a stronger preference for native plants than external feeders, probably because of their higher specificity (Kulfan et al 2010;Burghardt and Tallamy 2013;Kirichenko et al 2013).…”
Section: Discussionsupporting
confidence: 87%
“…Factors affecting the recruitment of exotic plants by indigenous herbivores have been studied through literature reviews and meta-analyses (e.g., Leather 1986;Brän-dle and Brandl 2001;Liu and Stiling 2006;Brändle et al 2008;Bezemer et al 2014), or field data on single or a small group of species (e.g., Siemann et al 2006;Parker and Gilbert 2007;Ando et al 2010;Harvey et al 2013;Castells et al 2014), but rarely through field data collected on a large number of species at the same place and the same time (Dietz et al 2004;Carpenter and Cappuccino 2005;Burghardt and Tallamy 2013;Dostál et al 2013). The examination of damage, population density and species richness in two functional groups of phyllophagous insects, leaf chewers and leaf miners allowed us to confirm the importance of some factors affecting the recruitment of exotic plants by phyllophagous insects, but not others.…”
Section: Discussionmentioning
confidence: 99%
“…This method confirms the ERH when the obtained results show that an alien species is attacked less than a co-occurring native congener. The pair I. parviflora -I. noli-tangere was tested by this method in the Czech Republic [43]. In that study, the compared plants showed similar damage caused by natural enemies, which is consistent with 60% of the results presented here.…”
Section: Discussionsupporting
confidence: 87%
“…For the tests, we used the alien Impatiens glandulifera and I. parviflora, and the native I. noli-tangere. Despite the very high invasiveness of both alien species [41], they have not been subjected to such tests in Poland at all, and rarely elsewhere in Europe [42][43][44]; this is surprising in view of the efforts made to develop biological control methods against these plants [45,46].…”
Section: Introductionmentioning
confidence: 99%
“…The first category of papers studied the responses of specialist and generalist native insect herbivores to invasive plants (Harvey et al 2010;Herrera et al 2011;Novotny et al 2003). The second category of papers compared the herbivory on native and invasive plants and subsequent changes in the levels of herbivory load, damage, and pollination (Ballard et al 2013;Dostál et al 2013;Maron and Vilà 2001).…”
Section: Introductionmentioning
confidence: 99%